EDUCATIVE PRACTICES IN DIABETES MELLITUS: A BIBLIOGRAPHICAL REVIEW - Elaine Cristina Barbui; Maria Inês Monteiro Cocco (Universidade Federal do Paraná, 1999)
Diabetes Mellitus is wordly thought to be a public health problem because it occupies an epidemiological position with high rates of incidence and prevalence, not considering the socioeconomical reverberations, translated by premature deaths, work inabilities and other cost associated to treatment. The aim of this study was to identify and analyze the literature referring to the educative practices in diabetes, in health journals, specifically for nurses in Brazil. We categorized such journals under three themes: the starting off of educative programs; motivation to self-care; educative actions in nursing. Educations in diabetes - cliente, family, professional - is of paramount importance to the diabetes people's life quality. Public policies in relation to health promotion doesn' t are refered in the literature analyses although have importance fundamental.